1997
DOI: 10.1093/ejo/19.1.21
|View full text |Cite
|
Sign up to set email alerts
|

In vitro measurement of orthodontic tooth movement in rats given  -aminopropionitrile or hydrocortisone using a time-lapse videotape recorder

Abstract: In vitro tooth movement of rat molars in response to an orthodontic force was recorded using a time-lapse videotape recorder and analysed by a computer system. Rats received daily s.c. injections of beta-aminopropionitrile (BAPN, 300 mg/kg/day) or hydrocortisone (10 mg/kg/day) for a period of 7 days. After drug administration, the animals were killed and the mandibles dissected. The jaw was then held under a stereomicroscope with a haemostatic clamp and an elastic band was inserted between the first and second… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0
5

Year Published

2001
2001
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(49 citation statements)
references
References 24 publications
0
44
0
5
Order By: Relevance
“…7,21 The prevalence of pathological processes treated by corticosteroids is widespread in the medical and dental practice, and the response from patients undergoing orthodontic treatment may differ from normal bone remodeling due to the use of these drugs. Figure 2 -Osteoclasts present in the Howship's lacunae, 7 days after application of orthodontic force in mice (hematoxylin-eosin, x400).…”
Section: Review and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7,21 The prevalence of pathological processes treated by corticosteroids is widespread in the medical and dental practice, and the response from patients undergoing orthodontic treatment may differ from normal bone remodeling due to the use of these drugs. Figure 2 -Osteoclasts present in the Howship's lacunae, 7 days after application of orthodontic force in mice (hematoxylin-eosin, x400).…”
Section: Review and Discussionmentioning
confidence: 99%
“…9 It has been shown that orthodontic movement can be affected by administration of pharmacological agents. 7,21 Corticosteroids are immunosuppressive and anti-inflammatory agents widely used to treat pathological processes in medical and dental practice, 11 in such a way that patients under orthodontic treatment may present variations in normal bone remodeling due to the use of these drugs. 7 Pithon and Ruellas 16 report as imperative the acquaintance about drugs mechanism by the Dental Surgeon, as well as possible interactions on orthodontic tooth movement that may occur, in order to benefit the treatment or adjust it to the effects on the stomatognathic system.…”
Section: Introductionmentioning
confidence: 99%
“…[15,16] Yamane et al found lower amount of tooth movement after hydrocortisone administration at a dose of 10 mg/kg/day for 7 days in rats and Davidovitch et al showed slower tooth movement in cats treated with cortisone acetate (12.5 to 25 mg/day). [17,18] Treatment with triamcinolone acetonide is associated with increased tooth movement in rabbits due to increased resorptive activity in the alveolar bone. [19] Another study on rats reported that prednisolone treatment did not affect the magnitude of orthodontic tooth movement as compared to control group.…”
Section: Corticosteroidsmentioning
confidence: 99%
“…48 It has been shown that orthodontic tooth movement can be affected by local or general administration of pharmacological agents. [48][49] However there are only a limited number of In 1992 an in-vivo study on white New Zealand rabbits was conducted to find out the effects of corticosteroid induced osteoporosis on orthodontic tooth movement. The researchers concluded that rabbits subjected to corticosteroid-induced osteoporosis undergo significantly more rapid orthodontic tooth movement and subsequent relapse than control animals.…”
Section: The Effects Of Corticosteroids On Orthodontic Tooth Movementioning
confidence: 99%
“…50 In 1997 an in vitro study carried out to measure orthodontic tooth movement in rats given betaaminopropionitrile (BAPN) or hydrocortisone using a time-lapse videotape recorder concluded that treatment with BAPN accelerated experimental tooth movements in vitro and hydrocortisone treatment inhibited the movements. 49 Another study carried out on rats in 2000, concluded that while there were no significant differences in the magnitude of tooth movement between the groups, steroid-treated rats displayed significantly less root resorption on the compression side and fewer TRAP (tartrate-resistant acid phosphatase) positive cells within the PDL(periodontal ligament) space on the same side. Thus they proposed that steroid treatment suppressed clastic activity.…”
Section: The Effects Of Corticosteroids On Orthodontic Tooth Movementioning
confidence: 99%